Role of vitamin D receptor (VDR) gene polymorphism in the pathogenesis of juvenile idiopathic arthritis: Theoretical and practical aspects - M. M. Kostik; L. A. Sheplyagina; V. I. Larionova (Современная ревматология, 2014)
Juvenile idiopathic arthritis (JIA) is a chronic inflammatory joint disease associated with impaired immune system performance. The specific features of JIA may be genetically determined.Objective: to assess JIA activity in children with vitamin D receptor (VDR) gene ApaI and BsmI polymorphism genotypes.Subjects and methods. The investigation enrolled 71 patients with JIA. When included in the investigation, all the patients were in an active state of disease. JIA activity was assessed using the most commonly used clinical and laboratory indicators, including the Ritchie articular index (RAI), JADAS10, JADAS27, JADAS71, CDAI, DAS, and DAS28. Molecular genetic studies determined VDR gene ApaI and BsmI polymorphisms by polymerase chain reaction, followed by restriction analysis.Results. The boys who were carriers of a bb BsmI polymorphic marker in the VDR gene had a significantly higher activity of JIA measured by RAI (p=0.03), DAS (p<0.05), JADAS10 (p=0.04), JADAS27 (p=0.04), and JADAS71 (p=0.04) than those who were carriers of B allele (BB + Bb genotypes).Conclusion. The carriage of the VDR gene bb BsmI genotype of the polymorphic marker is associated with high JIA activity, which may be regarded as a marker of poor prognosis in boys with JIA.